Ranolazine improved left ventricular diastolic functions and ventricular repolarization indexes in patients with coronary slow flow - Oksen, Dogac; Aslan, Muzaffer; Ozmen, Emre; Yavuz, Yunus Emre (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Coronary slow flow (CSF) is a condition commonly encountered during angiography. Recent studies have shown the adverse effects of CSF on left ventricular diastolic functions. CSF reportedly increases the novel ventricular repolarization parameters. Ranolazine is a preparation with a prominent anti-anginal activity that has positive effects on anti-arrhythmic and diastolic parameters. In this context, this study was carried out to investigate the effects of ranolazine on left ventricular diastolic functions and repolarization in patients with CSF.Material & Methods: Forty-six patients with CSF and 29 control subjects were included in the patient and control groups, respectively. Both groups received ranolazine for one month and were evaluated using 12-lead electrocardiography, conventional echocardiography, and tissue Doppler imaging at the baseline and after one month of ranolazine treatment. Results: Corrected P, QT dispersion, and Tp-e interval values were significantly higher in the patient group than in the control group. There was a significant decrease in isovolumic relaxation time (IVRT) and deceleration time (DT) values after the ranolazine treatment compared to the baseline values in the patient group but not the control group. A significant increase was observed in the mean E and A velocities and the mean E/A ratio after the ranolazine treatment compared to the baseline values in the patient group. Additionally, there was a significant difference between the Tp-e interval and corrected P dispersion values measured after the ranolazine treatment compared to the baseline values in the patient group but not in the control group. Conclusion: This study's findings demonstrated that ranolazine positively affected impaired diastolic functions and repolarization parameters, particularly in patients with CSF.